The Effects of Empathy-Training on Empathie Response Levels and Self- Concepts of Students in a Teacher-Training Program - Fraser, J. Alexander H.; Vitro, Frank T. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purposes of the study were to determine the effects of relatively short term empathy training on prospective teachers' empathie abilitiesand self-concepts. The experimental samples consisted of two intact groups of undergraduate students enrolled in a five week modular course in education entitled "Analysis of Self and Teacher Behavior." The two experimental groups received empathy training which consisted o practice responding to videotaped excerpts of counselling interviews, a filmed demonstration of empathie responding, and role-playing exercises.The findings indicated that empathy training resulted in statistically significant increases in levels of empathie ability for both experimental groups. Statistically significant changes in self-concept were found for one of the experimental groups and changes for the other experimental group, though not statistically significant were in a similar direction. Le but de la recherche était de déterminer les effets d'un entraînement de courte durée sur le développement, chez de futurs enseignants, de leurs capacités de comprehension d'autrui et de leur conception personnelle.Les sujets expérimentaux consistaient de deux groupes autonomes d'étudiants "sous-gradués" inscrits à un cours pilote de pédagogie intitulé "Autoanalyse et comportement pédagogique". Les deux groupes témoinsont subi un entraînement caractérisé par des réponses à des interviews d'orientation vidéo-enregistrées, par une démonstration filmée deréflexes de compréhension et par des reconstitutions de situations scolaires.Les résultats obtenus ont indiqué qu'un tel entraînement a suscité dans les deux groupes une hausse statistiquement significative des capacités de compréhension d'autrui. En ce qui concerne la conception personnelle, des modifications statistiquement significatives ont été enregistrées dans l'un des groupes, tandis que dans l'autre ont été notées des modifications dans le même sens bien que sans signification statistiqie.